BLEEDING FROM CORONARY ARTERY AND MAMMARY CORONARY GRAFTS INAPATIENTWITH STERNOMEDIASTINITIS AFTER CORONARY ARTERY BYPASS SURGERY - A. N. Vachev; V. K. Koryttsev; E. E. Adyshirin-Zade; V. V. Gladyshev (Вестник хирургии имени И.И. Грекова)
One of the most serious complications of sternomediastinitis after coronary artery bypass surgery is bleeding from coronary artery grafts. The result of successful treatment of the patient with purulent sternomediastinitis complicated by bleeding from the graft is presented. The choice of the method of stopping such bleeding is grounded.